The interrelationships between customer satisfaction, brand loyalty and relationship intentions of Generation Y consumers towards smart phone brands - P. G. Mostert; D. J. Petzer; A. Weideman (South African Journal of Business Management, 2016)
Smart phone marketers are finding it difficult to maintain market share in a market characterised by fierce competition and continued new product development. Generation Y consumers generally have a good command of technology and engage in technology-related behaviour such as texting, tweeting and web-surfing. When it comes to the adoption of smart phone applications, it is believed that Generation Y is leading the way. To retain Generation Y consumers, it is critical for organisations to ensure that customer satisfaction is achieved, brand loyalty has to be generated and meaningful long-term relationships with these consumers should be established. In this regard, this study aims to determine the interrelationships between customer satisfaction, brand loyalty and the relationship intentions of Generation Y smart phone users. Self-administered questionnaires were fielded among 395 Generation Y smart phone users living in Gauteng, South Africa. Results indicate significant and positive interrelationships between customer satisfaction, brand loyalty and relationship intention.
Keywords: 650